2006
DOI: 10.1152/ajpregu.00724.2005
|View full text |Cite
|
Sign up to set email alerts
|

Kupffer cell-generated PGE2triggers the febrile response of guinea pigs to intravenously injected LPS

Abstract: Because the onset of fever induced by intravenously (i.v.) injected bacterial endotoxic lipopolysaccharides (LPS) precedes the appearance in the bloodstream of pyrogenic cytokines, the presumptive peripheral triggers of the febrile response, we have postulated previously that, in their stead, PGE2 could be the peripheral fever trigger because it appears in blood coincidentally with the initial body core temperature (Tc) rise. To test this hypothesis, we injected Salmonella enteritidis LPS (2 microg/kg body wt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 77 publications
4
55
0
Order By: Relevance
“…It has also been established that hepatic vagal afferents are necessary to promptly convey information from the immune system to the hypothalamus and initiate a fever in response to peripheral LPS exposure (Simons et al, 1998;MohanKumar et al, 2000). In this regard it appears that interleukin-1beta or PGE 2 stimulates the vagus (Li et al, 2006;Wieczorek and Dunn, 2006), and these noradrenergic pathways project from the brainstem through the ventral noradrenergic bundle and synapse in the POAH, where there are numerous noradrenergic terminals (Kumar et al, 2007). Our work suggests that norepinephrine released from these projections may act quickly and directly at alpha-1 ARs to modulate the activity of thermosensitive and insensitive neurons to shift the set-point into a hyperthermic range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been established that hepatic vagal afferents are necessary to promptly convey information from the immune system to the hypothalamus and initiate a fever in response to peripheral LPS exposure (Simons et al, 1998;MohanKumar et al, 2000). In this regard it appears that interleukin-1beta or PGE 2 stimulates the vagus (Li et al, 2006;Wieczorek and Dunn, 2006), and these noradrenergic pathways project from the brainstem through the ventral noradrenergic bundle and synapse in the POAH, where there are numerous noradrenergic terminals (Kumar et al, 2007). Our work suggests that norepinephrine released from these projections may act quickly and directly at alpha-1 ARs to modulate the activity of thermosensitive and insensitive neurons to shift the set-point into a hyperthermic range.…”
Section: Discussionmentioning
confidence: 99%
“…New evidence suggests this peripheral febrile message is relayed to the hypothalamus via a much faster neural route, through the hepatic vagus to the nucleus tractus solitarius (NST; Blatteis, 2007). Upon arrival in the liver, LPS is taken up by Kupffer cells (Kc) and a complement cascade is activated, promoting Kc to release PGE 2 and stimulate hepatic vagal afferents that project to the POAH (Li et al, 2006). It is then the release of norepinephrine via the hepatic vagus which mediates this response to peripheral LPS (Feleder et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Its signaling starts with the recognition of pathogen-associated molecular patterns (PAMPs) and/or damageassociated molecular patterns (DAMPs) by immune cells (Atkins and Bodel, 1979;Blatteis, 2006). These stimuli, named exogenous pyrogens, are detected through germline-encoded pattern recognition receptors (PRR), a.e.…”
Section: Exogenous and Endogenous Pyrogensmentioning
confidence: 99%
“…Both COX2 (Steiner et al, 2005) and mPGES1 (Engblom et al, 2003) were shown to be indispensable for LPS-induced fever. In addition to the PGE 2 locally produced in the brain, PGE 2 can also be secreted at the periphery predominantly by hepatic and pulmonary macrophages (Li et al, 2006;Simm et al, 2016;Steiner et al, 2006). This peripheral PGE 2 binds to albumin which protects it from enzymatic degradation during its journey to the brain via the bloodstream (Ivanov and Romanovsky, 2004).…”
Section: The Key Role Of Pgementioning
confidence: 99%
“…This recognition mobilizes a cascade of events beginning with generation of complement (Blatteis et al, 2004), prostaglandin E 2 (PGE 2 ) (Li et al, 2006;Steiner et al, 2006), and the proinflammatory cytokines, tumor necrosis factor ␣, interleukin (IL)-1␤, and IL-6 (Luheshi, 1998;Dinarello, 1999). These downstream products of TLR4 activation activate the brain and vagal afferents (for review, see Maier et al, 1998) to induce further synthesis of prostaglandins (Cao et al, 1997;Matsumura et al, 2000;Yamagata et al, 2001) and cytokines within the brain that cause fever and sickness behavior (Dantzer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%